Teori Ruang dalam Sosiologi Perkotaan: Sebuah Pendekatan Baru - Dwianto, Raphaella Dewantari (UI Scholars Hub, 2012)
When New Urban Sociology (NUS) appeared in urban sociology in early 1970s in Europe, by including state and class, it offered a macro view point, to answer the insuficiency of micro frame which had been the characteristic of urban sociology from the Chicago School. However, along with the weakening of welfare state, NUS also lost its significance, and it then chose to deconstruct itself through theory of space. This paper tries to elaborate the origin of NUS and its development, putting it in the present context, to explore the possibility of perspective of the urban as the hub that connects community, state, and the global world.